Selected β-lactam resistance in selected species of gram-negative bacteria - Nelson, Elton (Department of Clinical Laboratory Sciences, 2026)
The molecular basis of β-lactam resistance was investigated in this study. Selected gram-negative clinical isolates potentially displaying therapeutic problems were chosen as the subjects. Clinical diagnostic tests are not always very accurate and informative about the molecular nature of β-lactam resistance, thus molecular investigations are carried out to more fully and comprehensibly explain the clinically observed phenomena. In the view of Enterobacteria being some of the most commonly isolated, clinically problematic, bacteria, E. coli and K. pneumoniae isolates with unusual β-lactam resistance profiles were investigated. The first cluster of E. coli isolates were investigated with respect to their resistance to the cephalosporins and the cephamycin, cefoxitin. β-lactamase promoter mutations were identified and expression studies were performed to corroborate overexpression of the AmpC enzyme. The second group of E. coli isolates displayed resistance to the inhibitor combination, amoxicillin-clavulanate. In this group, the resistance genes were identified, with their promoters. Resistance was attributed to TEM overproduction and overproduction of a specially adapted TEM (IRTs) β-lactamase. Primer extension was used to determine the transcriptional start site of the IRT. The K. pneumoniae isolates were investigated for their resistance to the cephalosporins, cefoxitin and amoxicillin clavulanate. The resistance was attributed to an interplay of β-lactamase production and the loss of permeability. Since A. baumannii is becoming an increasingly popular opportunistic pathogen in the clinical setting, strain RAN was also investigated. The presence of β-lactamase resistance genes was investigated. The chromosomal ampC gene was confirmed to be present, cloned and sequenced. The regulation of the ampC gene was examined. The ampC gene was also studied in terms of its genetic context. Sequence analysis suggests that the ampC might be associated with a stabilized transposition event.